I survived : the shark attacks of 1916 - Tarshis, Lauren (Tarshis, Lauren. I survived, 2010)
Ten-year-old Chet Roscow, who had been thrilled by the news of an aggressive great white shark attacking people all along the Atlantic coast, goes swimming with his friends in Springfield, New Jersey, one day, and wonders if he sees a shark in the water.